Intestinal occlusion due to diverticular disease of the colon (E.D.C.) - Asiner, Boris; Rodríguez de Vecchi, Víctor; Armand Ugon, César (Cirugía del Uruguay, 1974)
Intestinal occlusion due to diverticular disease of colon is a rare complication (less than 2 % of cases). Clinical and radiological aspects should be carefully considered. I'hose cases in which subocclusive manifestations or intermitent ( transitory) occlusion are found as part of symptomatology, should be excluded; the same applies to stenosis without clearly defined occlusion. Cases of chronic evolution may occur. Occlusion may originate in sigmoid colon -2 such patients within our case material- or more frequently in juxtalesional small intestine - 5 cases. This condition should be differentiated from ileal occlussion which may appear as a resuit of acute pericolodiverticulitis with involvement of peritoneum and possibility of aeroileocolia images, which appear contiguous. Palpation evidences pain and so does decompression. Auscultation indicates abdominal silence and transit does not totally cease. The possibility of colonic carcinoma should always be born in mind either as pause. or coincidence. The author analyzes tactical manage